New Perspectives on the Aging Lexicon. Issue 8 (August 2019) - Wulff, Dirk U.; De Deyne, Simon; Jones, Michael N.; Mata, Rui
Abstract : The field of cognitive aging has seen considerable advances in describing the linguistic and semantic changes that happen during the adult life span to uncover the structure of the mental lexicon (i.e., the mental repository of lexical and conceptual representations). Nevertheless, there is still debate concerning the sources of these changes, including the role of environmental exposure and several cognitive mechanisms associated with learning, representation, and retrieval of information. We review the current status of research in this field and outline a framework that promises to assess the contribution of both ecological and psychological aspects to the aging lexicon. Highlights: Past work suggests that normal and pathological aging are associated with changes in lexical and semantic cognition. We review recent evidence on how life span changes in size and structure of the mental lexicon impact lexical and semantic cognition. We argue that models of the aging mental lexicon must integrate both ecological and psychological factors and propose a research framework that distinguishes environmental exposure from cognitive mechanisms of learning, representation, and retrieval of information. Our framework emphasizes the need for interdisciplinary collaboration between linguistics, psychology, and neuroscience to generate insights into the ecological and computational basis of the aging mental lexicon.